2020
DOI: 10.2478/jvetres-2020-0074
|View full text |Cite
|
Sign up to set email alerts
|

Oestrus synchronisation with progesterone-containing sponge and equine chorionic gonadotropin in Pirlak ewes during the non-breeding season: can Toryum improve fertility parameters?

Abstract: IntroductionThe aim of the study was to determine the effect of the vitamins, omega-3 polyunsaturated fatty acid and minerals in the supplement Toryum administered before and during oestrus synchronisation on some fertility parameters of ewes during the non-breeding season.Material and MethodsThe experimental animals were clinically healthy Pirlak ewes, 55–75 days postpartum, aged 2–4 years and weighing 40–50 kg. A sponge was inserted into the vagina for 10 d (G1, n = 30; G2, n = 30) or 14 d (G3, n = 30; G4, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
3
12
0
1
Order By: Relevance
“…In addition, eCG treatment increases reproductive efficiency in such protocols (Kuru et al 2018a). In recent years, many studies have reported on the duration of the sponge in the vagina (Texeira et al 2016;Kuru et al 2017Kuru et al , 2018aKuru et al , 2020. Shortening of the sponge treatment length had no negative effect on fertility (Kuru et al 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, eCG treatment increases reproductive efficiency in such protocols (Kuru et al 2018a). In recent years, many studies have reported on the duration of the sponge in the vagina (Texeira et al 2016;Kuru et al 2017Kuru et al , 2018aKuru et al , 2020. Shortening of the sponge treatment length had no negative effect on fertility (Kuru et al 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…At 24 h after sponge removal, ewes were housed with rams for 4 d at a female:male ratio of 6:1. In a 4-d period, heat detection was made every 8 h. When the ewe mated, it was determined to be in heat and removed from the group (Kuru et al 2020).…”
Section: Oestrus Detection and Mating After Synchronizationmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Bu becerisi ile koyun ve keçilerde progesteron ile birlikte östrus senkronizasyonu ve ikizliği artırmak amacıyla sıklıkla kullanılmaktadır. [27][28][29] PMSG'nin sığırlarda kullanımı genel olarak ovulasyon oranını arttırmak üzerine denenmiş ve ovulasyon senkronizasyonu üzerine pozitif etkileri tespit edilmiştir. [30][31][32] Bu çalışmaların ortak yaklaşımı, ovulasyonu elde etmek amacıyla gerekli olan LH pikinin sağlanması amacıyla, PMSG'nin de kullanılabileceği üzerinde yoğunlaşmaktadır.…”
Section: Tartışma Ve Sonuçunclassified